Theonyms, Panthea and Syncretisms in Hittite Anatolia and Northern Syria Proceedings of the TeAI Workshop Held in Verona, March 25-26, 2022 - Warbinek, Livio; GIUSFREDI, FEDERICO (Studia Asiana, 2023)
The topic of the Anatolian panthea in the Bronze Age deals with Hattian, Hittite, Palaean, Luwian and Hurrian gods who have been worshiped in the Kingdom of Ḫatti. In such a context, along with trying to keep a balanced and methodologically-aware approach in our original research, we realized that a multi-authored work such as the present volume, with papers written by some of the major experts of Anatolian religious history, would represent an invaluable contribution to the advancement of a complex and vast field. This collection of essays is the result of the workshop Theonyms, Panthea and Syncretisms in Hittite Anatolia and Northern Syria, held at the University of Verona on 25th and 26th March 2022. Colleagues with different areas of expertise pertaining to the topic of Anatolian religions contributed to an extremely successful event.